ApoE4 requires lipidation enhancement to resolve cellular lipid and protein abnormalities following NPC1 inhibition - Erika Di Biase; Kyle J. Connolly; Ingrid Crumpton; Oliver Cooper; Penelope J. Hallett; Ole Isacson (Scientific Reports)
Abstract Apolipoprotein E (ApoE) variants are central to Alzheimer’s disease (AD), Lewy body dementia (LBD) and Niemann-Pick disease type C (NPC). The ApoE4 variant elevates AD risk by 3-15-fold. ApoE’s normal function in lipid transport is known. The question remains how different ApoE isoforms cause cellular pathogenesis. We determined the effects of ApoE isoforms on lipid accumulation induced by inhibiting the endo-lysosomal cholesterol transporter NPC1. In human fibroblasts and astrocytes, NPC1 inhibition caused a 4-fold cholesterol accumulation and mis-localization with altered cholesterol sensing and increased synthesis of cholesterol and triglycerides. Total APP, APP C-terminal fragments (CTF) and BACE1 levels increased 3-fold. Remarkably, the intracellular neutral lipids co-localized with APP and APP C-terminal fragments. ApoE2 and ApoE3, but not ApoE4, reduced intracellular cholesterol levels by 67% and 62%, respectively, normalized APP, BACE, CTF, and improved cell survival. ApoE4 combined with a synthetic lipopeptide, which increased the proportion of large lipidated ApoE4 particles, corrected these abnormalities. This highlights ApoE in lipid pathogenesis and targeting ApoE4 lipidation to restore ApoE4 function.